The Impact of Asymmetric Transistor Aging on Clock Tree Design Considerations - Firas Ramadan; Majd Ganaeim; Maayan Ella; Freddy Gabbay (IEEE Access)
Ensuring integrated circuits (ICs) operate reliably throughout their expected service life is more vital than ever, particularly as they become increasingly central to mission-critical applications. Advances in semiconductor technology have brought to light ICs’ vulnerability to various reliability challenges, notably those stemming from the phenomenon of transistor aging. Transistor aging refers to the progressive degradation of transistor performance over time. This degradation is predominantly due to bias-temperature instability (BTI), which can significantly undermine the reliability of ICs, leading to performance degradation and the potential for critical failures through timing violations. The situation is further complicated by the occurrence of asymmetric transistor aging, where the degradation is not uniformly distributed, thus intensifying timing violations and reliability concerns. Our study delves into the impact of asymmetric transistor aging on clock tree design and underscores the importance of useful skew, clock gating, and the variances between clock buffer delays and net delays in exacerbating timing violations. In response, we introduce extended timing constraints, clock tree antiaging circuitry, and an extended design flow aimed at alleviating the effects of asymmetric transistor aging on clock trees, thereby enhancing IC reliability. Our simulation analysis investigates the vulnerability of clock trees to asymmetric aging, using general-purpose graphics processing units (GPGPUs) as a case study, and highlights the resulting timing violations when factoring in asymmetric transistor aging. The antiaging circuitry and design flow are validated through aging-aware timing analysis, which confirms their effectiveness in eliminating the observed timing violations.